The Accountability of Village Fund Management: Study on Villages in the Sub-District of Dempet - Damayanti, Novia Vina; Hanafi, Rustam; Sutapa, Sutapa (Universitas Islam Sultan Agung, 2024)
Village fund accountability is the responsibility of the village government in managing village funds based on the village fund management law. This study aims to examine the effect of the competence of village apparatus, usage of information technology, community participation, internal control systems, and the application of administrative sanctions on village fund management accountability. The data source is from 62 village apparatus respondents from 16 villages in the Dempet sub-district. Data analysis uses multiple linear regression. The results of this study show that the competence of village apparatus, community participation, internal control systems, and the application of administrative sanctions have a significant positive effect on the accountability of village fund management. Meanwhile, the usage of information technology does not impact village fund management's accountability.